Analisis Kesalahan Penggunaan Kata Hasil Terjemahan Indonesia-Jepang dalam Karya Ilmiah Mahasiswa - Asep Achmad Muhlisian (Journal of Japanese Language Education and Linguistics, 2018)
ABSTRACTThe complexity of the translation process can lead to errors in translation. This case study analyzes the misuse of the Japanese word in Indonesian-Japanese translation. The data source is the nine scientific works of students majoring in Japanese. The results of the analysis show five categorizations of error: 1) Mistakes of inappropriate vocabulary in the sentence. 2) Error adding and omission of words in sentence, 3) Error writing letters saya, 4) Kanji writing error, and 5) error word change. The error is caused by five factors, namely, 1) Language Transfer, 2) Overgeneralization 3) Transfer of Training, 4) Learning Strategy 5) Communication Strategy.